The Role of Junior High Schools in Addressing Bullying: A Protective Framework for Victims - Kurniawan, Yunan Prasetyo; Jasmine, Zalika Averil (Faculty of Law, Universitas Lampung, 2024)
Bullying is a form of aggressive behavior often driven by anger or emotional distress, causing harm to others, particularly children. Legal protection for children in Indonesia is provided under Law No. 35 of 2014, amending Law No. 23 of 2002 on Child Protection, and reinforced by Permendikbudristek No. 46 of 2023 on the Prevention and Handling of Violence in Educational Units. These frameworks highlight the critical role of schools, especially educators, in safeguarding students. This research analyzes the role of junior high schools in addressing bullying and enforcing legal protections for child victims, using empirical legal research and a qualitative approach. Data were collected through interviews, observations, and document analysis at SMPN 17 South Tangerang City. The findings show that schools contribute significantly to bullying prevention through character education, anti-bullying initiatives, and collaboration with parents and external agencies. However, the implementation of legal protection for victims remains limited and needs to be strengthened.